Theoretical Modelling And Parameter Optimisation Of Ultrasonic Sewing Processes (Texas Journal of Multidisciplinary Studies, 2026)
In this work, a theoretical study of ultrasonic assisted sewing process is presented by focusing on three main functional stages; fabric feeding, needle penetration and the regulation of thread tension. The proposed approach is based on the integration of ultrasonic vibration into a conventional sewing machine to reduce contact friction, decrease needle penetration force, and improve the dynamic stability of yarn tension. The fabric-feeding process is modelled with an effective friction-reduction mechanism in which the apparent coefficient of friction decreases with the increase of the vibration velocity. This principle is in agreement with the previous works on ultrasonic friction reduction and vibration-assisted contact systems [1]–[6]. A model of fibrous materials using contact mechanics to describe the needle-penetration process is applied where ultrasonic excitation is caused by cyclic unloading, reduced needle-fiber friction and local thermomechanical softening [8]–[12]. Moreover, the thread-tension subsystem is modelled as a dynamic yarn system with wave propagation and closed-loop ultrasonic actuation, which is supported by recent studies on yarn-tension dynamics, vibration-based measurement, and piezoelectric control [15]–[19]. Based on the developed models, recommended operating ranges are determined for each module: 20–25 kHz for fabric feeding, 25–30 kHz for needle penetration and 20–25 kHz for thread-tension control. The respective amplitudes are chosen depending on the textile material and the functional task. The results provide a theoretical basis for the design of an integrated ultrasonic-assisted sewing platform with better process stability, lower mechanical load and higher stitch quality